Experiências auto relatadas de ambientes de atividades (SEAS-BR): validade para o Brasil - Peruzzo, Caroline Fernanda Bella (2024)
The Self-Reported Experiences of Activity Settings (SEAS) is a 22-item instrument designed to assess youths’ experiences in leisure activities, considering five areas: Personal Growth, Psychological Engagement, Social Belonging, Meaningful Interactions, and Choice and Control. The Brazilian version, SEAS-BR, was culturally adapted to assess the leisure experiences of Brazilian youth, being relevant for occupational therapy and inclusive interventions due to the lack of similar instruments. Objective: To validate the Brazilian version of SEAS-BR (Study 1) and to compare the choices of leisure activities of youths with typical development and physical disabilities (Study 2). The specific objectives were: (1) to evaluate its applicability in typical youths and those with physical disabilities (internal consistency); (2) to investigate discriminant validity between groups; (3) to verify the influences of gender, context, performance, and partners on the choice of activities. Method: Participants were 75 Brazilian young people, aged 14 to 23 years (50 with typical development and 25 with physical disabilities), fluent in Portuguese and with typical cognitive development (classified by the Mini Mental State Examination). Data were collected remotely (Google Forms and Google Meet) and in person (at locations chosen by the participants). Analyses were performed in SPSS 21, using the ChiSquare, Kolmogorov-Smirnov and Mann-Whitney U tests. Results: In study 1, the SEAS-BR showed high internal consistency, with Cronbach's alpha of 0.86 for typical young people and 0.91 for young people with physical disabilities. No significant differences were found between the remote and in-person collection modalities, indicating that both modalities are viable. Significant differences were observed between the typical and physically disabled groups in items related to mood (“excited”) and feelings during activities (“fun” and “interested”). In study 2, the leisure preferences of young people reflected sociocultural trends: boys preferred physical activities, while girls chose artistic and cultural practices. Young people with physical disabilities demonstrated greater adherence to sports activities, highlighting the importance of inclusive adaptations. Of the leisure categories, 9.3% of participants chose screenbased activities, 10.6% opted for musical activities, 44% for artistic and cultural activities, and 36% for sports activities. Significant differences were found in relation to learning new skills, improving in some activity, having good conversations, and personal development. Most young people (78.6%) chose group leisure activities, and these activities were associated with feelings of belonging, appreciation, and support, in addition to meaningful interactions, such as conversations and sharing of ideas. Conclusion: The SEAS-BR was validated as a reliable tool to assess the leisure experiences of typical young people and those with physical disabilities. This study reinforces the importance of expanding accessible and inclusive leisure options.